Improved gel-enhanced liquid chromatography-mass spectrometry by chemometrics for halal proteomics - Mohd Yusof, Mohd Hafis Yuswan; Wan Kamarudin, Wan Mohd Aizat; Mohd Desa, Mohd Nasir; Mohd Hashim, Amalia; Rahim, Nur Ajreena; Mustafa, Shuhaimi; Mohamed, Rozi; Lamasudin, Dhilia Udie (Elsevier BV, 2019)
Numerous analytical methods for the authentication of halal meat are now well established, with gel-enhanced liquid chromatography-mass spectrometry (GeLCMS) being a popular approach. However, the selection of potential protein markers on 1-dimensional gel electrophoresis (1DE) prior to LCMS is considered problematic, because using the optical density for the selection process could introduce human error. In this study, an improved GeLCMS method assisted by multivariate principal component analysis (PCA) was developed to identify the potential protein markers for non-halal pork among halal beef and chicken. The improved GeLCMS technique allowed for the confident excising of identified protein bands prior to in-gel tryptic digestion. The inferential protein markers (myofibrillar proteins), which might be present in the samples, were determined based on the identified sequence of peptides. This chemometric-assisted GeLCMS could potentially be used as a guideline to assist chemists in analysis of any gel-based separation of biomolecules, regardless of the field of study